Automatic partial discharge detection method of traction transformer based on wavelet transform. Issue 1 (1st February 2022) - Liu, Jiyong; Wang, Xin; Yan, Shengchun; Fan, Yan; Hao, Changjin
Abstract: Partial discharge parameter acquisition and storage of transformer lacks the setting of time threshold, which leads to the low reception rate of transformer discharge signal. An automatic detection method of partial discharge of transformer in substation based on wavelet transform is studied. By analyzing the ultrasonic waveform of discharge signal, the partial discharge parameters of transformer in high voltage substation are extracted. According to the principle of wavelet transform, the time threshold is set, the extracted parameters are collected and stored in sections, and the automatic detection algorithm of partial discharge parameters is established. By deriving the results, the automatic detection of partial discharge is completed. At this point, the design of automatic detection method for partial discharge of transformer in substation based on wavelet transform is completed. Analysis of experimental results: Through comparative experiments, it is found that the highest discharge signal receiving rate of this method is 87.5%, which is superior to other methods and has high application value.